2019
DOI: 10.1007/s10654-019-00585-4
|View full text |Cite
|
Sign up to set email alerts
|

Soy intake and breast cancer risk: a prospective study of 300,000 Chinese women and a dose–response meta-analysis

Abstract: Epidemiological evidence on the association of soy intake with breast cancer risk is still inconsistent due to different soy intake levels across previous studies and small number of breast cancer cases. We aimed to investigate this issue by analyzing data from the China Kadoorie Biobank (CKB) study and conducting a dose-response meta-analysis to integrate existing evidence. The CKB study included over 300,000 women aged 30-79 from 10 regions across China enrolled between 2004 and 2008, and followed-up for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Mucin contents influence the host’s signal transduction pathway to maintain intestinal morphological integrity [ 46 ]. It is known that Bifidobacterium adolescentis have anti-obesity and anti-inflammatory activities [ 47 ], and Faecalibterium prausnitzii is an excellent butyric acid-producer [ 42 ]. Butyrate can stimulate colon mucin and enhance the barrier capacity of the intestine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mucin contents influence the host’s signal transduction pathway to maintain intestinal morphological integrity [ 46 ]. It is known that Bifidobacterium adolescentis have anti-obesity and anti-inflammatory activities [ 47 ], and Faecalibterium prausnitzii is an excellent butyric acid-producer [ 42 ]. Butyrate can stimulate colon mucin and enhance the barrier capacity of the intestine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why some studies have shown an increased risk of developing breast cancer through ingestion of isoflavones [ 281 , 287 ], whilst other studies have not confirmed such associations or have shown the opposite [ 179 , 180 , 277 , 279 , 283 , 285 , 286 , 288 , 289 ], is probably due to the presence of the oestrogen receptors in the starting neoplasm [ 281 ], the population under study [ 290 ] or the physical form that the isoflavone that is consumed [ 288 , 291 ]. Meta-analyses of different studies in various populations generally support the idea that moderate to high consumption of a diet that contains isoflavones prevents EC, ovarian and breast cancer and its recurrence [ 283 , 292 , 293 , 294 ]. These data suggest that a diet rich in isoflavones or that concentrated soy supplements, which contain much higher isoflavone concentrations will be beneficial, but until more research is done with pre- and peri- and postmenopausal cohorts, a definitive conclusion cannot be met.…”
Section: Plant Derivatives and Hormonesmentioning
confidence: 99%
“…Recently, a large meta-analysis indicated that the dose of isoflavone is a critical factor for its effect in reducing breast cancer risk. This study showed that a higher amount of daily soy consumption, approximately 10 mg/day, decreased breast cancer risk by 3% (95% CI 1-5%) [37].…”
Section: Flavonoid/polyphenol Intake and Incidence Of Breast Cancermentioning
confidence: 73%